Dynamics in harmonious human-nature urban ecosystem model for environment sustainability: a review - Wu, Yuting; Azmi, Athira; Ibrahim, Rahinah; Abdulkareem Salih, Sarah; Abd Ghafar, Azmiah (UiTM Press, Universiti Teknologi MARA, 2024)
Abstract: In the face of growing urbanization, conflicts between human activities and the natural environment have resulted in increasingly evident problems, such as ecological degradation, excessive resource depletion, loss of biodiversity and pollution. These issues pose a growing threat to the achievement of global sustainable development goals. This study is part of a larger study to create a livable and sustainable urban environment. It aims to develop an urban ecosystem model for promoting harmony with nature by analyzing the latest literature research from 2019 to 2023 using the Systematic Literature Review method. This paper elucidates the latest research developments in urban design, urban ecosystems and the pursuit of enhanced synergy harmonious humans with nature. Subsequently, from the cross-analysis method it presents a synthesized model proposing a harmonious human-nature ecosystem for urban design. This model advocates for the cultivation of human natural identity, providing a framework to adapt, modify, and preserve the urban environment in harmony with nature. Such an approach is expected to enhance urban vitality that is in harmony between humans and nature while maintaining ecological functions and biodiversity and ensuring efficiency, equity, socio- cultural, and aesthetic values. This study contributes to identifying, understanding, and resolving ecological imbalances arising from urbanization. The results are expected to benefit authorities in maintaining a healthy standard of living in rapidly urbanizing areas. Future research will combine methods such as field investigations and design practices to further refine this urban design proposal, providing support and guidance for a more comprehensive sustainable urban environmental development.